Freedom of Thought, Conscience, and Religion under the ECHR, with Special Regard to Central Europe - Đukić , Dalibor (The ECHR at 70: The Central European Narrative, 2025)
The European Convention on Human Rights (ECHR) was drafted under the auspices of the Council of Europe (CoE) and specifies the fundamental substantive rights to be protected for citizens of CoE member states. This paper scrutinizes the ECHR provisions dealing with freedom of thought, conscience, and religion, and the relevant European Court of Human Rights (ECtHR) judgments concerning freedom of religion with a special emphasis on central European countries. The paper begins with a brief history of religious tolerance across the region of Central Europe. Considering the close relationship between the legal framework to protect religious freedom and the model of state-religion relations, the paper explores the system of cooperation between the state and religion, problems of concluding agreements between the state and religious groups, issues stemming from the multi-tiered registration systems, and conflicts between freedom of expression and freedom of religion. The analysed case law emphasises the importance of equal treatment of religious organisations, while the cooperation model of state-religion relations, which accommodates diverse religious needs, should be implemented in a manner that allows balancing between cooperation and discrimination concerns, as highlighted in the ECtHR rulings. Keywords: Freedom of thought, conscience, and religion, State-religion relations, multi-tiered registration systems, Central Europe